2016
DOI: 10.1016/j.ijcard.2016.02.146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dipeptidyl peptidase-4 inhibitors on heart failure: A meta-analysis of randomized clinical trials

Abstract: Please cite this article as: Kongwatcharapong J, Dilokthornsakul P, Nathisuwan S, Phrommintikul A, Chaiyakunapruk N, Effect of dipeptidyl peptidase-4 inhibitors on heart failure: A meta-analysis of randomized clinical trials, International Journal of Cardiology (2016Cardiology ( ), doi: 10.1016Cardiology ( /j.ijcard.2016 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 72 publications
1
39
0
1
Order By: Relevance
“…Use of saxagliptin significantly increased the risk of HF by 21% especially among patients with high CV risk (RR 1.215; 95% CI: 1.028 to 1.437; P=0.022), while others were not associated with an increased HF risk (31). Age ≥65 years, diabetes duration of ≥10 years and BMI ≥30 kg/m 2 were associated with an increased risk of HF among patients using saxagliptin (31). Based on available data, the risk of HF with DPP-4 inhibitors is of definitive concern and appears to be drug-specific.…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 96%
See 2 more Smart Citations
“…Use of saxagliptin significantly increased the risk of HF by 21% especially among patients with high CV risk (RR 1.215; 95% CI: 1.028 to 1.437; P=0.022), while others were not associated with an increased HF risk (31). Age ≥65 years, diabetes duration of ≥10 years and BMI ≥30 kg/m 2 were associated with an increased risk of HF among patients using saxagliptin (31). Based on available data, the risk of HF with DPP-4 inhibitors is of definitive concern and appears to be drug-specific.…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 96%
“…In a meta-analysis of 54 randomized controlled trials of DPP-4 inhibitors in 74,737 participants with a minimum follow-up of 12 weeks, DPP-4 inhibitors were not associated with an increased risk of HF compared to comparators (RR 1.106; 95% CI: 0.995 to 1.228; P=0.062) (31). The authors noted a differential effect of each DPP-4 inhibitor on the risk of HF.…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, these meta-analyses of RCTs with GLP-1RAs may be compared with those of RCTs with DPP-4 inhibitors [9,10], which showed that DPP-4 inhibitors were not associated with any increased risk of HF-related hospitalizations [10] except for saxagliptin [9], mainly because of the results of the SAVOR -TIMI 53 trial [7].…”
Section: Effects Of Liraglutide On Cardiac Function and Cardiovasculamentioning
confidence: 99%
“…HF is of major interest as it is the one cardiovascular outcome for which the risk has unequivocally been shown to be increased by some glucose-lowering therapies, particularly thiazolidinediones (glitazones) [4,5], whereas metformin appears to be safe [6]. Recently, some concerns have also been raised with the dipeptidyl peptidase (DPP)-4 inhibitor saxagliptin, following the publication of the Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus (SAVOR) -Thrombolysis in Myocardial Infarction (TIMI) 53 trial [7], a finding that casts some suspicion on the entire incretin-based pharmacological class [8][9][10]. In contrast, a marked, significant reduction in hospitalizations for HF has been reported with the sodium -glucose cotransporter type 2 (SGLT2) inhibitor empagliflozin in the Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients (EMPA-REG OUTCOME) [11,12].…”
Section: Introductionmentioning
confidence: 99%